Types Of Periphrases According To Social-Professional Classification - Ahmadova, Umida (FILOLOGIYA UFQLARI JURNALI, 2024)
The article provides information on the types of periphrases according to the social-professional classification. The importance of socially occupational classification of periphrases is widely elucidated. it also provides information on the types of classification and its place in linguistics.